An unexpected new genus of the relict nematocerous family Pachyneuridae (Diptera) from Japan - Saigusa, Toyohei; Emoto, Jun (Zootaxa, 2026)
Plesiopachyneura ohtaniensis gen. et sp. nov. of the rare nematocerous family Pachyneuridae is described and illustrated from Honshu, Japan. Plesiopachyneura is superficially similar to the genus Pachyneura, but distinguished from the latter by differences in the antenna, chaetotaxy of the tibiae, wing shape and venation, and female terminalia. Biogeography and bionomics of the new genus are briefly discussed.